Enhanced electrical conductivity and electromagnetic shielding properties of multi-component polymer/graphite nanocomposites prepared by solid-state shear milling - Xie Jiliang; Chen Li; Zeng Yanxia; Sun Xia; Xiao Xin (Nonlinear Engineering)
This study investigates a novel multi-component polymer composite method for preparing graphite/polymer composites with excellent electrical conductivity and electromagnetic shielding properties, aiming to address the challenges in achieving a balance between conductivity, mechanical stability, and thermal properties in applications like electronics, automotive, and aerospace. Expanded graphite (EG) was used as a conductive filler, and solid-state shear milling was employed to achieve uniform dispersion of graphite in a polymer matrix consisting of polyvinyl chloride (PVC), chlorinated polyethylene (CPE), and polyurethane elastomer (TPU), improving mechanical and thermal stability. X-ray diffraction, Raman spectroscopy, scanning electron microscopy, transmission electron microscopy, and conductivity tests revealed significant differences in graphite dispersion across substrates. In the EG/PVC-CPE system, graphite sheets are stripped into multiple layers, while in the EG/PVC-TPU system, they form thinner or even single layers, leading to enhanced conductivity and shielding efficiency. The results show that the EG/PVC-CPE and EG/PVC-TPU composites offer improved electrical and mechanical properties, demonstrating the potential of multi-component matrices and solid-state shear milling in developing high-performance composites for conductivity and electromagnetic interference shielding applications.